Police-initiated diversion for youth to prevent future delinquent behavior - Wilson, David B. (Campbell Systematic Reviews, 2018)
This Campbell systematic review examines the effects police-initiated diversion programs on delinquent behavior, compared to traditional system processing. The review summarizes evidence from nineteen high-quality studies, including 13 randomized controlled trials and six quasi-experimental studies.